SHOULDER PUT INTO EFFECT BY MEANS OF DEVELOPED LOW COST CPM MACHINE - Metan, S.S.; Mohankumar, G.C.; Krishna, Prasad (European Scientific Journal, ESJ, 2014)
Large number of technological advances that have recently been made in a wide variety of multidisciplinary fields, the boundary between engineering sciences and the relative applications to which they can be applied has become indistinct. Modern devices are being used in advanced mechanical, electrical, and computer systems for various applications, and to assist in research. Medi-mechatronics is the application of the mechatronics in the field of medical science. From the perspective of emerging trend in medical equipment in alteration from hydraulic driven systems to expand equipment functionality, reduce size and weight along with cleaner, safer, and environment friendly electromechanical system is a good choice. Continuous passive motion (CPM) is a widely used postoperative treatment method that is designed to aid recovery after joint surgery or injury. It can lead to a reduction in both hospital stay and analgesic requirement and accelerates the recovery process. In many physiotherapy centers the use of CPM is limited by the cost of the equipment. In the present work, design and development of the Low Cost Shoulder CPM Machine is successfully done. The cost of the machine has been reduced by 40% , without compromising the functionality and accuracy of the machine. The machine is tested at one of the renowned Hospitals in Sholapur-India. Thirty patients with shoulder related problems were exercised for different shoulder exercises on CPM machine for two io three weeks. Shoulder joint is observed to be enhanced to normal Range of Motion (ROM) and the patients’ pain level has been abridged.